2017
DOI: 10.1002/macp.201600553
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on Protecting Groups to Influence Vinyl Catechol Monomer Reactivity and Monomer Gradient in Carbanionic Copolymerization

Abstract: Several vinyl catechol‐based monomers with systematically varied acetal protecting groups suitable for carbanionic polymerization are introduced. All monomers are based on the 4‐vinyl benzodioxole or 5‐vinyl benzodioxole structure and differ in the nature of the protecting group for the catechol functionalities. Different symmetric ketones are used for the protection of the diol functionality. Polymers with average molecular weight from 2500 to 25 000 g mol−1 (Mw/Mn < 1.15) are obtained from homopolymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…10−15 Frey and co-workers recently reported living anionic polymerization of a cyclic acetal-protected 4-vinylcatecol; by subsequent deprotection of the resulting polymer, they could successfully achieve the tailored synthesis of poly(4-vinylcatecol). 16,17 On the other hand, direct living anionic polymerization of styrenes containing electrophilic groups such as cyano, N-alkylimino, N-arylimino, alkyl ester, aryl ester, N,N-dialkylamide, N,Ndialkylsulfonamide, and vinyl 18 was successfully demonstrated, 3,10,12 because in these cases, the propagating benzylic carbanions were effectively stabilized by the electron-withdrawing groups to prevent unwanted side reactions. 19,20 Recently, a styrene derivative possessing an electrophilic acyl group, 1-adamantyl 4-vinylphenyl ketone, was also shown to undergo living anionic polymerization with an organopotassium initiator in tetrahydrofuran (THF) at −78 °C.…”
Section: ■ Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…10−15 Frey and co-workers recently reported living anionic polymerization of a cyclic acetal-protected 4-vinylcatecol; by subsequent deprotection of the resulting polymer, they could successfully achieve the tailored synthesis of poly(4-vinylcatecol). 16,17 On the other hand, direct living anionic polymerization of styrenes containing electrophilic groups such as cyano, N-alkylimino, N-arylimino, alkyl ester, aryl ester, N,N-dialkylamide, N,Ndialkylsulfonamide, and vinyl 18 was successfully demonstrated, 3,10,12 because in these cases, the propagating benzylic carbanions were effectively stabilized by the electron-withdrawing groups to prevent unwanted side reactions. 19,20 Recently, a styrene derivative possessing an electrophilic acyl group, 1-adamantyl 4-vinylphenyl ketone, was also shown to undergo living anionic polymerization with an organopotassium initiator in tetrahydrofuran (THF) at −78 °C.…”
Section: ■ Introductionsupporting
confidence: 85%
“…Anionic polymerizations of various styrene derivatives have been widely studied to synthesize well-defined homo- and copolymers possessing predicted molecular weights and narrow molecular weight distribution (MWD). In fact, using suitable protecting groups or introducing electron-withdrawing groups, the range of functional styrene monomers, capable of undergoing living anionic polymerization, has been certainly expanded. Previous studies have demonstrated that a number of tailored polystyrenes possessing OH, SH, NH 2 , CHO, COCH 3 , COOH, CCH, and SiOH moieties could be synthesized by living anionic polymerization of suitably protected monomers. Frey and co-workers recently reported living anionic polymerization of a cyclic acetal-protected 4-vinylcatecol; by subsequent deprotection of the resulting polymer, they could successfully achieve the tailored synthesis of poly­(4-vinylcatecol). , On the other hand, direct living anionic polymerization of styrenes containing electrophilic groups such as cyano, N -alkylimino, N -arylimino, alkyl ester, aryl ester, N , N -dialkylamide, N , N -dialkylsulfonamide, and vinyl was successfully demonstrated, ,, because in these cases, the propagating benzylic carbanions were effectively stabilized by the electron-withdrawing groups to prevent unwanted side reactions. , Recently, a styrene derivative possessing an electrophilic acyl group, 1-adamantyl 4-vinylphenyl ketone, was also shown to undergo living anionic polymerization with an organopotassium initiator in tetrahydrofuran (THF) at −78 °C . Side reactions for this monomer could be avoided due to the presence of the bulky substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the catechol moiety has versatile adsorption behaviors towards a wide variety of substrates as seen in adhesive protein of mussel, such catechol‐containing polymers should be promising synthetic adhesives. [ 27–35 ]…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the catechol moiety has versatile adsorption behaviors towards a wide variety of substrates as seen in adhesive protein of mussel, such catechol-containing polymers should be promising synthetic adhesives. [27][28][29][30][31][32][33][34][35] The purpose of this study was to develop a series of welldefined vinyl catechol-containing copolymers using precision polymerization methodology. In this paper, we focused on ester protecting groups for vinyl catechol derivatives, using ester protecting groups which can be easily deprotected under moderate conditions effectively and selectively without forming detrimental by-products.…”
Section: Introductionmentioning
confidence: 99%
“…The use of renewable natural products is currently attractive from the viewpoint of sustainable developments both in science and industry. Some natural compounds contain phenolic catechol groups exhibiting important functions in nature, such as antisunburn, reductant, and curing functionalities. , For example, mussel adhesive protein contains catechol groups, which work on the surfaces of various substrates even in water. Therefore, vinyl monomers with catechol groups, including vinyl catechol (VC), have recently been intensely studied to mimic natural functions. A variety of protected VC monomers have been prepared and polymerized via radical and anionic polymerizations. We have also reported the synthesis of a vinyl catechol protected with two triethylsilyl groups (TES 2 VC) from 4-vinylguaiacol, which was derived from naturally occurring ferulic acid by decarboxylation followed by dealkylation with triethylsilane with a catalytic amount of B­(C 6 F 5 ) 3 . The resulting protected VC could be successfully polymerized using a reversible addition–fragmentation chain transfer (RAFT) radical polymerization and deprotected to afford well-defined poly­(vinyl catechol).…”
Section: Introductionmentioning
confidence: 99%